Traditional Chinese Medicine's "Yipingweiqi" Adjusts Homeostasis of Tumor Immune Microenvironment - Wang, Runxi; Yang, Shuhan; Fang, Liyuan; Wang, Yan; Xie, Yi; Liu, Suying; Fang, Yuhang; Zhang, Ying (Zhongliu fangzhi yanjiu, 2023)
Tumor immune microenvironment has been the focus of tumor research in recent years, and its role in tumor regulation has become prominent and has received increasing attention. The imbalance of the tumor immune microenvironment plays an important role in promoting tumor progression, and the adjustment of its instability plays an important role in controlling tumor progression. The theoretical idea of Traditional Chinese Medicine's "Yipingweiqi" is basically the same as that of modern medicine of controlling tumors by maintaining the balance of the immune microenvironment. This study discusses the aspects of tumor immune microenvironment, its destabilization, relationship to tumor progression, importance in Traditional Chinese Medicine, and regulation by Traditional Chinese Medicine with different treatments. In particular, this work focuses on the role of Traditional Chinese Medicine in maintaining the balance of the tumor immune microenvironment and its potential mechanism by using qi benefit, yang warming,